ChemInform Abstract: A New Family of Wurtzite‐Phase Cu2ZnAS4‐x and CuZn2AS4 (A: Al, Ga, In) Nanocrystals for Solar Energy Conversion Applications. Issue 11 (February 2016) - Ghosh, Anima; Palchoudhury, Soubantika; Thangavel, Rajalingam; Zhou, Ziyou; Naghibolashrafi, Nariman; Ramasamy, Karthik; Gupta, Arunava
Abstract: Cu2 ZnMS4‐x (M: Al, Ga, In) nanocrystals are prepared by the colloidal hot‐injection method starting with thermal decomposition of a 2:1:1 molar mixture of Cu(acac)2, Zn(acac)2, and M(acac)3 in oleylamine under N2 (Schlenk line, 150 °C) followed by quickly injecting a mixture of n‐dodecanethiol and tert‐dodecanethiol and subsequent heating (250 °C, 1 h), with the latter leading to a structural transition from the wurtzite to the stannite phase.